Bifunctional Therapeutic Peptide Assembled Nanoparticles Exerting Improved Activities of Tumor Vessel Normalization and Immune Checkpoint Inhibition. Issue 12 (22nd May 2021) - Taleb, Mohammad; Atabakhshi‐Kashi, Mona; Wang, Yazhou; Rezvani Alanagh, Hamideh; Farhadi Sabet, Zeinab; Li, Fenfen; Cheng, Keman; Li, Chen; Qi, Yingqiu; Nie, Guangjun; Ying, Zhao
Abstract: The effectiveness of cancer immunotherapy is impaired by the dysfunctional vasculature of tumors. Created hypoxia zones and limited delivery of cytotoxic immune cells help to have immune resistance in tumor tissue. Structural and functional normalization of abnormal tumor vasculature provide vessels for more perfusion efficiency and drug delivery that result in alleviating the hypoxia in the tumor site and increasing infiltration of antitumor T cells. Taking advantage of peptide amphiphiles, herein, a novel peptide amphiphile nanoparticle composed of an antiangiogenic peptide (FSEC) and an immune checkpoint blocking peptide ( D PPA) is designed and characterized. FSEC peptide is known to be involved in vessel normalization of tumors in vivo. D PPA is an inhibitory peptide of the PD‐1/PD‐L1 immune checkpoint pathway. The peptide amphiphile nanoparticle sets out to test whether simultaneous modulation of tumor vasculature and immune systems in the tumor microenvironment has a synergistic effect on tumor suppression. Increased intratumoral infiltration of immune cells following vascular normalization, and simultaneously blocking the immune checkpoint function of PD‐L1 reactivates effective immune responses to the tumors. In summary, the current study provides a new perspective on the regulation of tumor vessel normalization and immunotherapy based on functional peptide nanoparticles as nanomedicine for improved therapeutic purposes. Abstract : The current study provides a new perspective on the combination of tumor vessel normalization and immunotherapy using a bifunctional peptide nanoparticle as nanomedicine to improve the therapeutic outcomes. The manipulation of the vasculature network is a promising new strategy that in combination with immune checkpoint inhibitors enhances the immunotherapy of solid tumors.